Failure of sodium hypochlorite to meet the EN 1500 efficacy requirement for hygienic hand disinfection. (March 2023) - Suchomel, M.; Gebel, J.; Kampf, G.
Summary: This study evaluated the bactericidal efficacy of two alternative hand antiseptics, based on sodium hypochlorite or sodium hypochlorite and hypochlorous acid, compared with isopropanol on the hands of volunteers artificially contaminated with Escherichia coli using EN 1500. The reference alcohol was applied according to the norm, and the study formulations were used as in common practice (3 mL for 30 s). The products showed mean log10 reductions of 1.63 and 1.89, both of which were inferior to the reference treatment (4.78). Due to the failure to achieve sufficient bactericidal efficacy within 30 s, sodium hypochlorite (0.05–0.06%) should not be considered for hand disinfection.